2020
DOI: 10.1002/ajoc.201900717
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Synthesis of Diphosphorous Quinoline Compounds

Abstract: Herein, we report the reaction of quinoline with diphenylphosphine oxide in the presence of visible light without catalyst. The reaction completes in 24 h under the mild conditions and the substrates are well tolerant. This method provides a straightforward and environmentally friendly access to diphosphorous quinoline compounds. Similarly, this method can also aid in the phosphate functionalization of some heterocyclic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…36 In 2020, Xiong et al reported that direct C–H phosphorylation of heteroarenes could be carried out under visible light irradiation without using any photocatalysts (Scheme 22). 37 They mainly focused on the diphosphorylation of quinoline derivatives using diphenylphosphine oxides as phosphorylating agents. During the optimization of the reaction conditions, they found that the best result was obtained by carrying out the reaction using K 2 S 2 O 8 as an oxidant, trifluoroacetic acid as an additive in MeCN–H 2 O (1 : 1) under the irradiation of a household 24 W CFL.…”
Section: C–p Bond Formation Via C–h Functionalizationmentioning
confidence: 99%
“…36 In 2020, Xiong et al reported that direct C–H phosphorylation of heteroarenes could be carried out under visible light irradiation without using any photocatalysts (Scheme 22). 37 They mainly focused on the diphosphorylation of quinoline derivatives using diphenylphosphine oxides as phosphorylating agents. During the optimization of the reaction conditions, they found that the best result was obtained by carrying out the reaction using K 2 S 2 O 8 as an oxidant, trifluoroacetic acid as an additive in MeCN–H 2 O (1 : 1) under the irradiation of a household 24 W CFL.…”
Section: C–p Bond Formation Via C–h Functionalizationmentioning
confidence: 99%
“…The C-H phosphonation of the quinoline ring is a highly efficient method for accessing its phosphorylated derivative. The C5-H phosphonation of 8-aminoquinoline amides has been realized by Qiao et al [105] using silver salts; however, the method suffers from stoichiometric metal salts, a high reaction temperature and a limited substrate scope [Figure 69]. Furthermore, the C4-H phosphonation of 8-aminoquinoline amide remains elusive.…”
Section: Dehydrogenative C-h Phosphorylationmentioning
confidence: 99%
“…Wang et al. reported the photocatalytic synthesis of di‐phosphorous quinoline compounds under nitrogen environment in the presence of persulfate K 2 S 2 O 8 and trifluoroacetic acid (TFA) (Scheme 1a‐2) [9b] . Liang and co‐workers achieved C( sp 2 )−H phosphorylation using RuCl 3 ⋅3H 2 O as the photocatalyst, K 2 S 2 O 8 as the oxidant, AgNO 3 as the additive and NaOAc as the base (Scheme 1a‐3) [9c] .…”
Section: Introductionmentioning
confidence: 99%